The Usage of Isoguarantees for Currency Portfolio and Integrated Asset and Liability Management - Rutkauskas, Aleksandras Vytautas (Ekonomika, 2003)
This article suggests using the idea of isoguarantees or the management of complicated financial processes and other processes depending upon them or in some way joining them together, emphasizing the importance of guaranty and reliability management. Financial risk investigations let us talk about commensurability of the amount of most of the financial indicators and the risk.There are some conceptions quite uncommon in financial literature, which, however, are necessary needed in order to analyze reliability of expected results using methods mentioned in the article. One of those conceptions is isoguarantee, which is a line joining effectiveness (profit profitability, incomes etc) indicators of the same guarantee in the possibilities - risk plane.Using ideas and techniques of Markowitz or modern portfolio and adequate with stochasticity of profit possibilities portfolio, integrated assets and liabilities portfolio is being offered, which helps to put in order the possibilities of analyzed process or subject expansion according to its levels of guaranties. Two academic examples are shown as an illustration for ideas analyzed: formation of currency portfolio and formation and management of integrated assets and liabilities portfolio. And so the article is divided into two parts.Although the methods of analytic solution search are sometimes used in the analysis of cases, still the main method for analyzing complicated cases remains imitative technologies that can be under stood as an interaction of computer counting and imitative modeling. Obtained results are shown in the geometric form. It is also necessary to admit that computer resources sometimes were not sufficient to present continuous processes in visually adequate discrete manner.To analyze extremely complicated situations huge resources of computer power and velocity are needed, but taking into account the fact that innovations outrun demand in this area, imitation technologies should be recognized as the most perspective mean of analysis of complicated quantitative cases helping to solve any analytical problem successfully.